The Influence of Product Quality and Price Perception on Gold Purchasing Decisions at the Slamet Jaya Shop, Surabaya - Akbar, M. Rizal; Fitriyah, Zumrotul (International Journal of Economics (IJEC), 2024)
The aim of this research is to determine the influence of product quality and price perception on the decision to purchase gold products at the Slamet Jaya store in Surabaya. The population in this study are consumers who own gold in Surabaya who have made purchases at the Slamet Jaya gold collection in Surabaya. The sample in this study was 98 respondents taken using a purposive sampling technique, namely taking samples based on criteria. The sample collected of respondents who had purchased gold products at Take Slamet Jaya Surabaya. The data used in this research are primary and secondary data. The analysis technique used in this research is (PLS) with validity test and hypothesis testing. The results of this research prove that: (1) product quality has a positive and significant effect on purchasing decisions (2) price perception has a positive and significant effect on purchasing decisions.